Etiological Factors& Clinical Courses of Birth Asphyxia in Rural and Urban Population of Kishanganj District. (Bangladesh Journal of Medical Science, 2017)
Problem statement : perinatal asphyxia, neonatal or birth asphyxia is a medical condition from deprivation of oxygen to a newborn infant long enough during the process to cause physical usually to the brain. And it is almost all neonatal deaths occur in our rural and urban area. Where the majority is delivered at homes with negligible antenatal care and poor prenatal services.Methods: In this collaborative study conducted prospective, descriptive study. As a case of 150 newborn babies and as a control 1190 newborn babies are fulfilled the selection criteria for prenatal and birth asphyxia .Results: Incidence of birth asphyxia in relation to ante partum and intrapartum factors. And shows that mother with complication like eclampsia, APH, PROM, cord accidents, failed progress of labor, obstructive labor & prolong 2nd stage of labor, etc were more likely to deliver asphyxiated baby, and analysis of maternal risk factors for birth asphyxia. Many pathological, biochemical & metabolic changes occurs as a result of birth asphyxia. And the data were analyzed by slandered statistical test, namely, Z test, Chi square test, and uniovariate and ultivariate logistic regression analysis of risk factor.Conclusion: In our study it was observed that, Pregnancy related complication in rural & urban population of Kishanganj district was mostly Eclampsia, pre-eclamptic toxaemia, Oligohydramnios, PROM(M24hr) etc. To prevent birth asphyxia trained personal and neonatal resuscitation equipment should be mandatory in all maternity home/hospital because prevention is the best and be only option to reduce the Pre natal & birth asphyxia.Bangladesh Journal of Medical Science Vol.16(4) 2017 p.554-556